Three-Dimensional (3-D) Reconstructions of EISCAT IPS Velocity Data in the Declining Phase of Solar Cycle 23 - Bisi, M. M.; Jackson, B. V.; Breen, A. R.; Dorrian, G. D.; Fallows, R. A.; Clover, J. M.; Hick, P. P. (Solar Physics, 2010)
The European Incoherent SCATter (EISCAT) radar has been used for remote-sensing observations of interplanetary scintillation (IPS) for a quarter of a century. During the April/May 2007 observing campaign, a large number of observations of IPS using EISCAT took place to give a reasonable spatial and temporal coverage of solar wind velocity structure throughout this time during the declining phase of Solar Cycle 23. Many co-rotating and transient features were observed during this period. Using the University of California, San Diego three-dimensional (3-D) time-dependent computer assisted tomography (C.A.T.) solar-wind reconstruction analysis, we show the velocity structure of the inner heliosphere in three dimensions throughout the time interval of 20 April through 20 May 2007. We also compare to white-light remote-sensing observations of an interplanetary coronal mass ejection (ICME) seen by the STEREO Ahead spacecraft inner Heliospheric Imager on 16 May 2007, as well as to in-situ solar-wind measurements taken with near-Earth spacebourne instrumentation throughout this interval. The reconstructions show clear co-rotating regions during this period, and the time-series extraction at spacecraft locations compares well with measurements made by the STEREO, Wind, and ACE spacecraft. This is the first time such clear structures have been revealed using this 3-D technique with EISCAT IPS data as input.